2018
DOI: 10.1515/opag-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters estimation in quantitative traits of a cross of triticale (x Triticosecale W.)

Abstract: Triticale (x Triticosecale Wittmack) is a cereal used in Argentina as a winter seasonal pasture or feeding grain. Efforts made on breeding have led to varieties with potential grain yield similar or greater than with wheat. The aim of this study was to determine the gene effects, heritability, genetic gain, heterosis and inbreeding depression in various quantitative traits of a cross from contrasting lines of triticale using generation means analysis. The thousand kernel weight was adjusted to a model of addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
2
0
0
Order By: Relevance
“…Dominance (h) and dominance×dominance (l) epistatic gene effects had a similar sign; which suggested complementary epistatic effects for CHL. Compared to what is reported in the literature, the results of the present study corroborate findings of Ferrari et al (2018), who observed that for GY additive (d) gene effect was not significant, but dominance (h) and dominance×dominance (l) epistatic effects made the higher contribution to the inheritance of this trait. For this character, Ljubičić et al (2016) reported duplicate type epistasis, proposing to delay selection for this trait because of the narrow range of variability and high probability of low selection success in an early generation.…”
Section: Gene Effectssupporting
confidence: 87%
“…Dominance (h) and dominance×dominance (l) epistatic gene effects had a similar sign; which suggested complementary epistatic effects for CHL. Compared to what is reported in the literature, the results of the present study corroborate findings of Ferrari et al (2018), who observed that for GY additive (d) gene effect was not significant, but dominance (h) and dominance×dominance (l) epistatic effects made the higher contribution to the inheritance of this trait. For this character, Ljubičić et al (2016) reported duplicate type epistasis, proposing to delay selection for this trait because of the narrow range of variability and high probability of low selection success in an early generation.…”
Section: Gene Effectssupporting
confidence: 87%
“…Some environments may trigger the activation of environments-specific genes or mask the gene's effects [48]. Heritability is another parameter that shows how genetic gain could be expected [49]. Except for BM, SPW, and BMYLD, moderate to high broad-sense heritability was found for yield and yield-related traits (Table S2), which is consistent with reports from previous studies by Garcia et al [50] and Al-Tabbal and Al-Fraihat [51].…”
Section: Discussionsupporting
confidence: 89%